2008
DOI: 10.4161/auto.6401
|View full text |Cite
|
Sign up to set email alerts
|

Quantitation of autophagy by luciferase release assay

Abstract: Autophagy is a cellular process that has been defined and analyzed almost entirely by qualitative measures. In no small part, this is attributable to the absence of robust quantitative assays that can easily and reliably permit the progress of key steps in autophagy to be assessed. We have recently developed a cell-based assay that specifically measures proteolytic cleavage of a tripartite sensor protein by the autophagy protease ATG4B. Activation of ATG4B results in release of Gaussia luciferase from cells th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
71
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(72 citation statements)
references
References 73 publications
1
71
0
Order By: Relevance
“…A similar procedure has been reported before. 15 Basically, HEK-293T cells (human embryonic kidney cells, ATCC, CRL-11268) were seeded in 6-well plate with a density of 70% confluence. One microgram of enzyme expression plasmid and 2 μg of substrate expression plasmid were cotransfected …”
Section: ■ Experimental Methodsmentioning
confidence: 99%
“…A similar procedure has been reported before. 15 Basically, HEK-293T cells (human embryonic kidney cells, ATCC, CRL-11268) were seeded in 6-well plate with a density of 70% confluence. One microgram of enzyme expression plasmid and 2 μg of substrate expression plasmid were cotransfected …”
Section: ■ Experimental Methodsmentioning
confidence: 99%
“…All three proteins have previously been found to be valuable markers of autophagy also when fused to fusion partners such as green fluorescent protein (GFP) and luciferase. 13,17,19,[21][22][23][24] To estimate the autophagic flux of these proteins we developed an inducible expression system to monitor their degradation following promoter shut-off (Fig. 1B).…”
Section: Resultsmentioning
confidence: 99%
“…5), suggesting a role for ATG4B phosphorylation in promoting the binding of ATG4B with LC3-PE and hence aiding in LC3 delipidation. Using the Actin-LC3B-dNGLUC assay, which serves as a cell-based assay to detect the cleavage of both pro-LC3 and LC3-PE (31,32,34), we showed that activity of the ATG4B S383A/S392A mutant toward LC3 cleavage was greatly decreased. It is possible that phosphorylation of the flexible C-terminal region of ATG4B induces a conformation where accessibility of ATG4B to its membraneassociated substrate, LC3-PE is more favorable.…”
Section: Discussionmentioning
confidence: 99%
“…The evidence for an important role of phosphorylation in controlling ATG4B's LC3-directed protease activity included experiments in which ATG4B recovered from cells was dephosphoryated in vitro using phosphatases and studies of phosphorylation site mutants (particularly the S383A, S392A double mutant) recovered from cells. For these experiments, the protease activity of ATG4B was measured in vitro using an engineered substrate LC3-PLA 2 and in intact cells using the substrate actin-LC3B-dNGLUC assay (27,29,34). Using these assays, we found that phosphorylation-site mutants of ATG4B showed reduced cellular protease activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation